ANIMAL AL-JALLALAH AND ITS LAWS: CASE STUDY IN MALAYSIA - Betania Kartika Mufih (Pondok Pesantren Modern Islam Assalaam, 2017)
As Muslims, we have been guided by God in the Qur’an regarding halal and unlawful food to eat. In the Surah al-Maidah, verse 3 states: “Forbidden to you (eat) carcasses, blood, pork, meat of animals slaughtered in the name other than Allah, choked, beaten, fallen, gored, save that which ye have slaughtered, and forbidden for you that are slain for idols. And it is forbidden to draw fate with the arrow (to draw fate with the arrow) is wickedness “. In addition to those mentioned in the Qur’an, there is a type of animal called al-Jallalah also included in food that is forbidden to eat. Al-Jallalah is a halal animal to eat, four legged (ruminan) or two-legged (poultry), and the basic food is dirt and unclean. The 73th Bureau of Malaysia’s Fatwa Nationality Authority in 2006 has decided aquatic fsh are also haram eaten if the fsh is deliberately kept in unclean water or deliberately fed unclean such as pork, carcasses and others. The issue of fshery in a place mixed with pig droppings has links with al-Jallalah animals which is an important aspect in the Islamic fqh perspective. The purpose of this study is to explain and understand the concept of animal al-Jallalah on catfsh in terms of defnition, fsh food, pond environment and quarantine period. In this study, the method used is the study of libraries, for discussion of sources naqli and aqli against legal problems, also through inductive methods (istiqra’i) as well as the use of several methods of feld investigation such as interviews and experiments / experiments. This review will help to improve the quality of halal fsh. Muslims need to refer to the latest fatwa, especially the material is originally halal and can be turned into haram including syubhah with contaminated with various materials and processes that halal status is doubtful.